THEMATIC PROGRESSION PATTERNS IN ELT JOURNAL ABSTRACTS - Rahman, Kasyfur; Arrafi’i, M. Arsyad; Imansyah, Imansyah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
Developing an English cohesive and coherent writing requires an effort of connecting ideas grammatically and semantically. To explore this, we carried out a research study by analyzing fifteen journal abstracts from international journals in ELT whose impact factors are within the top 10 in the field. The data showed that the abstracts make use of integrated pattern, not relying simply upon a single pattern. The findings also suggest ambiguous relationship between some clauses, many of which rather represent inductive relationship; therefore coding them into the three thematic progression patterns in Eggins (1994) seemed to be less accommodating. Further research on this subject would then require more sophisticated research theoretical framework.